2017
DOI: 10.1177/1060028017709820
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Antimicrobial Stewardship Interventions in the Emergency Department

Abstract: AMS interventions in the ED may improve patient care. However, the optimal combination of interventions is unclear. Additional studies with more rigorous design evaluating core components of AMS programs, including prospective audit and feedback are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 56 publications
(200 reference statements)
1
40
0
Order By: Relevance
“…feedback on behaviour) have shown more promise. For example, a systematic review exploring effectiveness of antimicrobial stewardship interventions within the emergency department found that studies which employed audit and feedback strategies achieved statistically significant increases in appropriateness of antimicrobial prescribing and adherence to guidelines, as well as decreases in antimicrobial use [74]. Similarly, primary research exploring audit and feedback interventions in settings such as a tertiary care hospital [75] and an intensive care unit [76] found reduced use of antibiotics such as fluoroquinolones by 2.3 defined daily doses/1000 patient-days [95% CI − 3.97 to − 0.63] and significant reductions of antimicrobial use by 24.3% (87.3 defined daily doses/100 beds vs. 66.1 defined daily doses/100 beds; P < 0.001) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…feedback on behaviour) have shown more promise. For example, a systematic review exploring effectiveness of antimicrobial stewardship interventions within the emergency department found that studies which employed audit and feedback strategies achieved statistically significant increases in appropriateness of antimicrobial prescribing and adherence to guidelines, as well as decreases in antimicrobial use [74]. Similarly, primary research exploring audit and feedback interventions in settings such as a tertiary care hospital [75] and an intensive care unit [76] found reduced use of antibiotics such as fluoroquinolones by 2.3 defined daily doses/1000 patient-days [95% CI − 3.97 to − 0.63] and significant reductions of antimicrobial use by 24.3% (87.3 defined daily doses/100 beds vs. 66.1 defined daily doses/100 beds; P < 0.001) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Also relevant to ambulatory patients in the ED, multiple studies identified in the review demonstrated that clinical pharmacists reviewing culture results after discharge have improved appropriateness of antibiotic prescribing. Regarding the quality of the available evidence, all but one of the studies assessed had a high risk of bias or failed to provide sufficient methodologic information to complete the assessment . This highlights the need for improved study design including reporting antibiotic utilization and clinical outcomes by age group in future ED‐based antibiotic stewardship intervention studies.…”
Section: Ambulatory Care Stewardship Interventionsmentioning
confidence: 99%
“…Although data exists demonstrating the benefit of stewardship initiatives in the ED, there are still a multitude of disease states where additional opportunities exist for stewardship. Losier et al conducted a systematic review including 43 studies, which also concluded that antimicrobial stewardship interventions in the ED may improve patient care [34]. The authors focused more specifically on pharmacist involvement in stewardship efforts within the ED, however, they acknowledged that the optimal combination of interventions is still unclear.…”
Section: Discussionmentioning
confidence: 99%